Molecular Insight into the Interaction Mechanisms of Amino-2H-Imidazole Derivatives With BACE1 Protease: A QM/MM and QTAIM Study - Vega Hissi, Esteban Gabriel (2015)
In this study, we described quantitatively the interactions between two new amino-2H-imidazole inhibitors ((R)-1t and (S)-1m) and BACE1 using a hybrid quantum mechanics-molecular mechanical (QM/MM) method together with a quantum theory of atoms In Molecules (QTAIM) analysis. Our computational calculations revealed that the binding affinity of these compounds is mostly related to the amino-2H-imidazole core, which interact tightly with the aspartate dyad of the active site. The interactions were stronger when the inhibitors presented a bulky substituent with a hydrogen bond acceptor motif pointing toward Trp76, such as the 3,5-dimethyl-4-methoxyphenyl group of compound (S)-1m. Furthermore, the QTAIM analysis revealed that many hydrophobic interactions complement cooperatively the hydrogen bond which is not present when compound (R)-1t is bound to the enzyme. The combined QM/MM-QTAIM analysis allows identifying the interactions that account for the activity difference between compounds, even at a nanomolar range.